Współpraca przedsiębiorstw w dziedzinie innowacji - Szulczyńska, Urszula (Companies' Cooperation in the Field of Innovation, 2006)
Although an innovative activity is used as an instrument of competition, cooperation in this field creates completely new quality. It causes, that competition among individual subjects changes into competition among nets of companies. In case, when the net constitute enterprises traditionally competing, because of similar resources and capabilities, competition among them in some fields vanishes. It is natural, that enterprises creating value chain tend to be more competitive. The aspiration is reflected in cooperation in the field of innovative activities among suppliers and customers. The author analyzes scope of the cooperation and its effect for collaborating firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 630-637